The Genius of France Triumphant.- or - Britannia petitioning for Peace- vide The Proposals of Opposition. - To the Patriotic Advocates for Peace, this Seemly sight is dedicated. - Gillray, James, 1756-1815 ? (Humphrey, H., 1795)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Fox, Charles James, 1749-1806; Sheridan, Richard Brinsley, 1751-1816; Britannia (Symbolic character); Great Britain -- Politics and government -- 1760-1820 -- Caricatures and cartoons